More than a woman, nothings stops the rain - 911; Virgin Records; Windswept Pacific Music (London : Virgin Records, 1998)
Contains two tracks of a version of Bee Gees classic which were a huge hit in the 70's.
More Than A Woman (Barry Gibb/Maurice Gibb/Robin Gibb) -- Nothing Stops The Rain (McLaughlin/Constable/Brennan/Dawbarn/Douglas).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English